THE EFFORTS TO REDUCE DEPRESSION LEVELS IN THE ELDERLY USING MUSIC THERAPY TECHNIQUES: UPAYA PENURUNAN TINGKAT DEPRESI PADA LANSIA DENGAN MENGGUNAKAN TEHNIK TERAPI MUSIK - Hyan Oktodia Basuki; Hanim Nur Faizah; Andini Vina Azzahra; Ananda Khoirunnisa; Dellanikita (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2024)
Background: Depression is a disorder of mental feelings that often occurs in society. Starting from untreated stress can turn into more serious. Depression can occur at all ages, especially in the elderly, the elderly are a group that is vulnerable to physical and psychosocial changes. Purpose: This community service activity aims to socialize about treatment in reducing depression/stress by using music therapy. Method: This community service activity uses the lecture and question and answer method. The lecture method is carried out by presenting material about depression and music therapy.Meanwhile, the question-and-answer method is done by asking participants about the material that has been presented. Result: The results of this community service activity found that participants could understand and apply the material that had been presented. Conclusion: Based on the community service activities that have been carried out, many of the participants are enthusiastic about receiving the whole series of events, starting from the presentation of the material to the question-and-answer interaction. Keywords: Depression, Music Therapy, Elderly